Method for preparing magnesium alloy material through lattice defect regulation and control
Through the combination of pre-compression deformation and low-temperature heat treatment, a large number of dislocations and twin defects in magnesium alloys are introduced, and the alloy elements are promoted to aggregate and precipitate at these defects, forming high-density nano-precipitation phases, which solves the improvement of traditional magnesium alloys The problem of decreasing plasticity during strength has achieved a coordinated improvement in strength and plasticity.
Patent Information
- Application Number
- CN202411626398.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-21
AI Technical Summary
In the process of increasing strength of traditional magnesium alloys, the plasticity of traditional magnesium alloys often decreases significantly, resulting in brittle fractures in actual applications, and the strength and plasticity cannot be improved synergistically.
Through the combination of precompression deformation and low-temperature heat treatment, a large number of dislocations and twin defects are introduced, and the alloying elements are promoted to aggregate and precipitate at these defects, forming a high-density nano-precipitation phase.
It is achieved that the strength of the magnesium alloy is significantly improved without significantly sacrificing the plasticity of the magnesium alloy, and to a certain extent the plasticity of the material is maintained or improved, achieving coordinated optimization of strength and plasticity.
Smart Images

Figure CN119491127A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of magnesium alloys, and in particular to a method for preparing magnesium alloy materials by regulating lattice defects. Background Art
[0002] my country's magnesium ore resources account for more than 70% of the world's magnesium resources. It is a major producer and exporter of magnesium alloy materials and has significant strategic advantages. From the perspective of lightweight, the density of magnesium alloy is low, only one-fourth of steel and two-thirds of aluminum alloy. It can greatly reduce the weight of products at the same strength, which helps to improve automobile fuel efficiency, reduce energy consumption and environmental pollution, and is an important material for achieving energy conservation, emission reduction and green development.
[0003] In the fields of aerospace, transportation, oil and gas extraction, and medical equipment, magnesium alloys have significant application advantages. These fields often have strict requirements on the mechanical properties of materials, requiring both high strength to withstand complex working environments and good plasticity to ensure the machinability and safety of materials. However, a core problem of traditional magnesium alloys is the contradiction between strength and plasticity. In order to improve the strength of magnesium alloys, the method commonly used in the prior art is precipitation strengthening. In order to achieve a greater precipitation strengthening effect, it is often necessary to add a high content of alloying elements. Although this strategy can significantly improve the strength of the material, the addition of a high content of alloying elements will induce the precipitation of a larger second phase, increase the stress concentration inside the material, and reduce the ability of plastic deformation. At the same time, the crystal structure of magnesium alloys determines that it has poor plasticity at room temperature, especially in the process of increasing strength, the plasticity tends to drop significantly. This means that when the strength of magnesium alloys is improved by adding alloying elements or changing the processing technology, the ductility and toughness of the material will be affected, resulting in the material being prone to brittle fracture in practical applications. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a method for preparing magnesium alloy materials by utilizing lattice defect regulation, so as to solve the problem in the prior art that microstructure regulation cannot achieve a coordinated improvement in plasticity and strength.
[0005] In order to solve the above technical problems, this application adopts the following technical solutions:
[0006] A method for preparing a magnesium alloy material by regulating lattice defects, the specific steps are as follows:
[0007] Step 1: First, accurately batch the ingredients, heat pure Mg until it is melted, add pure Zn, Mg-Ce master alloy and Mg-Nd master alloy after melting, and introduce inert protective gas at the same time;
[0008] Step 2: heating the melt obtained in step 1 to completely melt it, and then keeping it at the temperature for 20 to 30 minutes to obtain a magnesium alloy melt;
[0009] Step 3: pouring the magnesium alloy melt obtained in step 2 into a preheated mold for die casting, and obtaining a magnesium alloy ingot after cooling;
[0010] Step 4: heating and homogenizing the magnesium alloy ingot obtained in step 3;
[0011] Step 5: extruding the magnesium alloy treated in step 4 at 350° C. to 450° C., with an extrusion rate of 1 to 10 mm / s and an extrusion ratio of 10 to 50;
[0012] Step 6: The magnesium alloy treated in step 5 is subjected to a heat treatment at 300°C to 450°C for 1 to 12 hours, and subjected to a pre-compression deformation treatment; wherein, the pre-compression deformation is 1% to 15% and the strain rate is 10 -2 ~10 -4 / s;
[0013] Step 7: heat treating the magnesium alloy obtained in step 6 to obtain the magnesium alloy material;
[0014] Calculated by mass percentage, in the magnesium alloy material, the Zn content is 0.5% to 1%, the Ce content is 0.1% to 0.3%, the Nd content is 0.3% to 0.6%, and the remainder is magnesium and unavoidable impurity elements.
[0015] Preferably, in step 7, the heat treatment is: keeping warm at 100° C. to 260° C. for 2 h to 24 h.
[0016] Preferably, in step 4, the conditions for the heating homogenization treatment are: homogenization treatment at 400° C. to 480° C. for 8 h to 24 h.
[0017] Preferably, in step 1, pure Mg is smelted at 700°C to 720°C; the inert gas is a mixture of CO2 and SF6; after the inert protective gas is introduced, the temperature is kept at 650°C to 700°C for 20 to 40 minutes.
[0018] Preferably, in the mixed gas, the volume ratio of CO2 and SF6 is (200-400):1.
[0019] Preferably, in step 2, the melt is heated to 720° C. to 750° C. and then kept warm.
[0020] Preferably, in step 3, the mold is preheated to 200°C to 350°C.
[0021] Preferably, the ultimate compression rate of the magnesium alloy material at room temperature is at least 35%.
[0022] Compared with the prior art, this application has the following beneficial effects:
[0023] 1. The present application improves the preparation method of magnesium alloy. After the magnesium alloy is subjected to heating and homogenization treatment, the magnesium alloy is obtained by extrusion, and then the magnesium alloy is subjected to pre-compression deformation treatment. A large number of lattice defects such as dislocations and twins are introduced into the magnesium alloy matrix through pre-compression deformation; these defects not only change the microstructure of the alloy, but also provide favorable conditions for the precipitation behavior in the subsequent heat treatment process; the formation of dislocations and twins not only increases the work hardening effect of the alloy, but also provides effective nucleation sites for the segregation of alloy elements, making the alloy more prone to phase change and element segregation in the subsequent heat treatment process.
[0024] 2. The present application performs heat treatment on the magnesium alloy that has undergone pre-compression deformation treatment, thereby activating the formation and growth of precipitation phases; on the basis of pre-compression deformation, the heat treatment allows the alloy elements to stably precipitate at the lattice defects to form a high-density nano-precipitate phase; these precipitates are not only small in size but also evenly distributed, thereby enhancing the strength of the alloy; on the other hand, the presence of the nano-precipitate phase hinders dislocation movement and twin expansion, thereby dispersing internal stress concentration and improving the alloy's ability to resist deformation.
[0025] 3. The combination of the sixth step of pre-compression deformation and the seventh step of heat treatment in the method described in the present application has a significant effect on the microstructure and mechanical properties of the Mg-Zn-Ce-Nd magnesium alloy: the pre-compression deformation introduces a large number of lattice defects in the microstructure of the magnesium alloy, including dislocations, twins, etc.; the heat treatment promotes the segregation of alloying elements in lattice defects and the formation of fine precipitates; through the synergistic effect of these two steps, the alloy not only achieves a significant improvement in strength, but also maintains plasticity to a certain extent, thereby achieving a synergistic enhancement of strength and plasticity. It is worth noting that during the heat treatment process, the element segregation behavior mainly occurs on Zn and Nd. These two elements segregate together at dislocations and twin boundaries, but the Ce element hardly segregates and precipitates at any defect position. This shows that the method described in the present application has obvious selectivity in inducing the behavior of alloying elements to segregate and precipitate at defects. The Ce element has a good effect of promoting non-basal slip in the matrix, thereby improving the plasticity of the alloy. The uniform distribution of the Ce element in the magnesium alloy matrix also makes the Mg-Zn-Ce-Nd magnesium alloy material treated by the method described in this application have almost no loss of plasticity on the basis of significantly improved strength, and the plasticity can reach more than 35%, ultimately achieving a synergistic improvement in material strength and plasticity, making it have good application prospects in the automotive, aerospace, electronic and communication equipment, medical equipment and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 BF-STEM images of the alloys of Comparative Example 1 and Example 4; wherein a and b are for Comparative Example 1, and c and d are for Example 4; dislocations are represented by small black arrows, and twin boundaries are represented by small red arrows.
[0027] Figure 2 It is the HAADF-STEM of the alloy of Example 4 and its Mapping element distribution map; wherein, a is the HAADF-STEM map, b is the Mg element distribution map, c is the Zn element distribution map, d is the Nd element distribution map, and e is the Ce element distribution map.
[0028] Figure 3 This is the BF-STEM image of Comparative Example 2.
[0029] Figure 4 It is a graph showing the changes in mechanical properties of Comparative Example 1 and Examples 2 to 4; wherein a is a typical compression engineering stress-strain curve, and b is the changes in mechanical property parameters. DETAILED DESCRIPTION
[0030] This application will combine the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on this application belong to the scope of protection of this application.
[0031] Unless otherwise indicated in specific cases in this application, the numerical ranges listed herein include the upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values listed when defining the range.
[0032] 1. A method for preparing magnesium alloy materials by regulating lattice defects
[0033] Step 1: First, accurately batch the ingredients, heat pure Mg until it is melted, add pure Zn, Mg-Ce master alloy and Mg-Nd master alloy after melting, and introduce inert protective gas at the same time;
[0034] Step 2: heating the melt obtained in step 1 to completely melt it, and then keeping it at the temperature for 20 to 30 minutes to obtain a magnesium alloy melt;
[0035] Step 3: pouring the magnesium alloy melt obtained in step 2 into a preheated mold for die casting, and obtaining a magnesium alloy ingot after cooling;
[0036] Step 4: heating and homogenizing the magnesium alloy ingot obtained in step 3;
[0037] Step 5: extruding the magnesium alloy treated in step 4 at 350° C. to 450° C., with an extrusion rate of 1 to 10 mm / s and an extrusion ratio of 10 to 50;
[0038] Step 6: The magnesium alloy treated in step 5 is subjected to a heat treatment at 300°C to 450°C for 1 to 12 hours, and subjected to a pre-compression deformation treatment; wherein, the pre-compression deformation is 1% to 15% and the strain rate is 10 -2 ~10 -4 / s;
[0039] Step 7: heat treating the magnesium alloy obtained in step 6 to obtain the magnesium alloy material;
[0040] Calculated by mass percentage, in the magnesium alloy material, the Zn content is 0.5% to 1%, the Ce content is 0.1% to 0.3%, the Nd content is 0.3% to 0.6%, and the remainder is magnesium and unavoidable impurity elements.
[0041] After studying the prior art, the present application found that in the field of materials science, especially for the development of lightweight alloys, improving the strength and plasticity of materials has always been the focus of research. However, while traditional methods enhance the strength of alloys, they often lead to a decrease in their plasticity. This inverse relationship between strength and plasticity limits the practical application of many high-performance alloys. For example, although traditional heat treatment processes can improve the mechanical properties of alloys by adjusting the internal structure of materials, in the process of pursuing high strength, it is inevitable to sacrifice the plasticity and toughness of materials, which largely restricts the scope of application of alloys, especially in industries such as aerospace and automobile manufacturing that require high load-bearing capacity and good formability. The present application is conceived to attempt to regulate the internal structure of magnesium alloy materials by improving the preparation method, and to control the formation of the second phase by using different defects formed, so as to improve the strength of magnesium alloys without significantly sacrificing the plasticity of magnesium alloys.
[0042] Based on the above ideas, the present application adjusts the method for preparing magnesium alloys and proposes an innovative alloy strengthening strategy, that is, by combining pre-strain with intermediate annealing, the contradiction between strength and plasticity in the traditional method is effectively solved. The present application can generate a large number of dislocations and defects inside the magnesium alloy by pre-compression deformation treatment of the extruded magnesium alloy material. These dislocations and defects can not only provide more active points for subsequent heat treatment, but also promote the segregation of specific alloy elements at the locations of dislocations and defects and the formation of fine precipitation phases, thereby achieving the strengthening effect. More importantly, the introduction of pre-compression deformation treatment does not sacrifice the plasticity of the material like the traditional method, but enhances the plasticity of the material to a certain extent. This is because the defects generated by pre-strain can promote the formation of nanophases in the subsequent heat treatment process. These nanophases can effectively pin dislocations and twins, thereby maintaining or even improving the plasticity of the material while improving the strength. Further microscopic analysis shows that the nanophase formed under the combined action of pre-compression deformation treatment and low-temperature heat treatment is the key to achieving the goal of synergistic optimization of alloy strength and plasticity. These nanophases are mainly composed of Zn and Nd elements, which tend to segregate at dislocations and twin boundaries to form discontinuously distributed small-sized precipitates, which play a vital role in strengthening the alloy. In addition, the present application also found that the alloy strengthening strategy designed in the present application is selective for the induction of alloy elements, and the Ce element hardly segregates and precipitates at the defect position, indicating that the segregation behavior of alloy elements under defect induction has obvious element selectivity, which also provides new ideas for the design of future alloy composition.
[0043] In some embodiments of the present application, the present application obtains an extruded magnesium alloy after processing by step 5, because compared with the cast state, the extruded alloy has fewer internal defects, better comprehensive mechanical properties, and is more conducive to subsequent processing. In step 5, the magnesium alloy treated in step 4 is extruded at 350°C to 450°C. If the temperature is too high, the surface of the extruded bar will be overburned, increasing the surface defects of the alloy, and the dimensional accuracy of the alloy bar will be seriously affected. If the temperature is too low, the alloy bar is difficult to deform, the extrusion process is difficult to achieve, and a qualified alloy bar cannot be obtained. Therefore, the temperature of magnesium alloy extrusion can be 350°C, 400°C, 450°C, etc., and all ranges and sub-ranges between the above values; the extrusion rate is controlled at 1 to 10 mm / s, and extrusion too slow will cause abnormal growth of grains in the organization, while affecting the surface quality of the alloy bar; extrusion too fast will cause incomplete recrystallization of the organization, increase the content of organizational defects, and affect the plasticity of the alloy bar. Therefore, the extrusion rate of the magnesium alloy can be 1mm / s, 2mm / s, 3mm / s, 4mm / s, 5mm / s, 6mm / s, 7mm / s, 8mm / s, 9mm / s, 10mm / s, etc., and all ranges and sub-ranges between the above values; at the same time, the extrusion ratio is controlled between 10 and 50. Too low an extrusion ratio will affect the recrystallization behavior of the alloy and reduce the extrusion effect; too high an extrusion ratio will make it difficult to extrude, increase the internal stress of the rod, and cause the alloy rod to undergo early aging during the deformation process, which is not conducive to the subsequent processing of the magnesium alloy material. Therefore, the extrusion ratio can be 10, 15, 20, 25, 30, 35, 40, 45, 50, etc., and all ranges and sub-ranges between the above values; it should be understood that in the implementation scheme, any of the above ranges can be combined with any range of other reaction conditions in the present invention.
[0044] In some embodiments of the present application, in step 6, the magnesium alloy treated in step 5 is subjected to a heat treatment at 300°C to 450°C for 1 to 12 hours, and is subjected to a pre-compression deformation treatment; wherein, the pre-compression deformation is 1% to 15% and the strain rate is 10 -2 ~10 -4 / s. Pre-compression strain is the process of introducing a large number of dislocations and twins into the matrix of magnesium alloy materials. These defects not only change the microstructure of the alloy, but also provide abundant active points for subsequent heat treatment. When the alloy is subjected to pre-compression strain, the atomic arrangement inside the material changes significantly, forming a lens-shaped twin structure and a network dislocation structure. These structural changes provide favorable conditions for subsequent heat treatment. During the pre-compression strain process, solute atoms (such as Zn and Nd) begin to segregate at dislocations and twin boundaries. These segregated solute atoms provide the necessary prerequisites for the subsequent formation of precipitation phases. Pre-compression strain also increases the defect energy inside the material, making it easier for solute atoms to segregate at defects, thereby providing an energy driving force for the subsequent formation of precipitation phases. The segregation of these solute atoms and the increase in defect energy lay the foundation for the formation of nano-precipitation phases during subsequent heat treatment, allowing fine precipitation phases to be more effectively pinned on dislocations, thereby improving the strength of the alloy. In the present application, the magnesium alloy after the treatment in step 5 is subjected to a heat treatment at 300°C to 450°C for 1 to 12 hours. If the heat treatment temperature is too high at this time, the alloy will be overburned, thereby affecting the quality of the alloy. However, if the heat treatment temperature is too low, the homogenization effect will be reduced. Therefore, the heat treatment temperature is 300°C, 350°C, 400°C, 450°C, etc., as well as all ranges and sub-ranges between the above values; if the heat treatment time is too short, the homogenization effect cannot be achieved, and if it is too long, it will have an adverse effect on the magnesium alloy material, resulting in a reduction in the homogenization effect. Therefore, the heat treatment time is 1h, 4h, 8h, 10h, 12h, etc., as well as all ranges and sub-ranges between the above values; next, the magnesium alloy material is subjected to a pre-compression deformation treatment at the heat treatment temperature; wherein, calculated according to the percentage of length change, the pre-compression deformation amount is 1% to 15%, and the strain rate is 10 -2 ~10 -4 / s. The present application found that too small a pre-compression deformation will lead to insufficient defect introduction and affect the precipitation strengthening effect; while too large a pre-compression deformation will lead to excessive defects such as twins and dislocations, thus affecting the plasticity of the alloy. Therefore, calculated according to the percentage of length change, the pre-compression deformation can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, etc., as well as all ranges and sub-ranges between the above values; not only the pre-compression deformation should be controlled, but also the strain rate should be controlled to be within 10 -2 ~10 -4 / s, because too slow a strain rate will lead to a long loading time and affect processing efficiency; too fast a strain rate will lead to excessive concentration of stress inside the material and cause material failure. Therefore, the strain rate is 10 -2 / s, 10 -3 / s, 10 -4 / s, etc., and all ranges and sub-ranges between the above numerical values; it should be understood that, in an embodiment, any of the above ranges can be combined with any ranges of other reaction conditions in the present invention.
[0045] In some embodiments of the present application, step 7 is also crucial in the present application, which further promotes the segregation of solute atoms at dislocations and twin boundaries. At high temperatures, the diffusion rate of solute atoms increases, allowing more solute atoms to gather at defects. These segregated solute atoms begin to form precipitates. These precipitates are usually nanoscale, with a size between 2 and 20 nm. The formation of precipitates not only increases the strength of the material, but also improves the plasticity of the material by pinning dislocations and twin boundaries. The present application further found that precipitates can be divided into two types: one is a precipitate with less element segregation, uniform contrast and small size; the other is a precipitate with more element segregation, discontinuous distribution, and a size between 5 and 20 nm. These precipitates are mainly composed of Zn and Nd elements, while Ce elements are hardly segregated and precipitated at defect locations, which indicates that the segregation of alloy elements under defect induction has obvious element selectivity. The formation of these nano-precipitates significantly improves the strength of the alloy. The precipitated phases hinder the movement of dislocations by pinning dislocations and twin boundaries, thereby improving the yield strength of the material. In addition, the high-density nano-precipitated phases and pinned dislocations in the magnesium alloy material matrix can disperse the stress concentration formed by dislocations during subsequent deformation, thereby synergistically improving the strength and plasticity of the magnesium alloy. The twin boundaries remain stable during pre-compression strain and low-temperature heat treatment, further improving the strength and plasticity of the material. Therefore, through the combination of pre-compression strain (step 6) and low-temperature heat treatment (step 7), the microstructure of the magnesium alloy has changed significantly, forming high-density nano-precipitated phases and stable twin boundaries. These structural changes not only significantly improve the strength of the alloy, but also maintain the plasticity of the material to a large extent, achieving synergistic optimization of strength and plasticity. In step 7, the heat treatment is: keeping warm at 100℃~260℃ for 2h~24h. If the heat treatment time is too short or the temperature is too low, it is difficult for the solid solution atoms to fully diffuse to form a precipitated phase; if the heat treatment time is too long or the temperature is too high, the precipitated phase will grow abnormally, affecting the precipitation effect of the nanophase. Therefore, the heat treatment temperature can be 100°C, 150°C, 200°C, 260°C, etc., and all ranges and sub-ranges between the above values; the insulation time can be 2h, 4h, 8h, 12h, 16h, 20h, 24h, etc., and all ranges and sub-ranges between the above values; it should be understood that, in an embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.
[0046] In some embodiments of the present application, in step 1, pure Mg is smelted at 700°C to 720°C; the inert gas is a mixed gas of CO2 and SF6; after the inert protective gas is introduced, the temperature is kept at 650°C to 700°C for 20 to 40 minutes. In the mixed gas, the volume ratio of CO2 to SF6 is (200 to 400):1. The pure Mg smelting temperature can be 700°C, 710°C, 720°C, etc., and all ranges and sub-ranges between the above values; under the protection of inert protective gas, the holding temperature can be 650°C, 680°C, 700°C, etc., and all ranges and sub-ranges between the above values; the holding time can be 20min, 30min, 40min, etc., and all ranges and sub-ranges between the above values; in the mixed gas, the volume ratio of CO2 and SF6 can be 200:1, 300:1, 400:1, etc., and all ranges and sub-ranges between the above values; it should be understood that in the implementation scheme, any of the above ranges can be combined with any range of other reaction conditions in the present invention.
[0047] In some embodiments of the present application, in step 2, the melt is heated to 720°C to 750°C, and then kept warm. The melt can be heated to 720°C, 730°C, 750°C, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.
[0048] In some embodiments of the present application, in step 3, the mold is preheated to 200° C. to 350° C. The mold can be preheated to 200° C., 300° C., 350° C., etc., and all ranges and sub-ranges between the above values; it should be understood that in an embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.
[0049] In some embodiments of the present application, in step 4, the conditions for the heating homogenization treatment are: homogenization treatment at 400°C to 480°C for 8h to 24h. In this step, if the heating homogenization treatment temperature is too low, the eutectic structure will not be easily melted, affecting the homogenization effect; and if the heating homogenization treatment temperature is too high, the material surface will be overburned and the quality requirements of the heat-treated material cannot be met. Therefore, the heating homogenization treatment temperature is 400°C, 440°C, 450°C, 460°C, 480°C, etc., and all ranges and sub-ranges between the above values; the homogenization treatment time can be 8h, 12h, 24h, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.
[0050] In some embodiments of the present application, the present application obtains an extruded magnesium alloy after processing by step 5, because compared with the cast state, the extruded alloy has fewer internal defects, better comprehensive mechanical properties, and is more conducive to subsequent processing. In step 5, the magnesium alloy treated in step 4 is extruded at 350°C to 450°C. If the temperature is too high, the surface of the extruded bar will be overburned, increasing the surface defects of the alloy, and the dimensional accuracy of the alloy bar will be seriously affected. If the temperature is too low, the alloy bar is difficult to deform, the extrusion process is difficult to achieve, and a qualified alloy bar cannot be obtained. Therefore, the temperature of magnesium alloy extrusion can be 350°C, 400°C, 450°C, etc., and all ranges and sub-ranges between the above values; the extrusion rate is controlled at 1 to 10 mm / s, and extrusion too slow will cause abnormal growth of grains in the organization, while affecting the surface quality of the alloy bar; extrusion too fast will cause incomplete recrystallization of the organization, increase the content of organizational defects, and affect the plasticity of the alloy bar. Therefore, the extrusion rate of the magnesium alloy can be 1mm / s, 2mm / s, 3mm / s, 4mm / s, 5mm / s, 6mm / s, 7mm / s, 8mm / s, 9mm / s, 10mm / s, etc., and all ranges and sub-ranges between the above values; at the same time, the extrusion ratio is controlled between 10 and 50. Too low an extrusion ratio will affect the recrystallization behavior of the alloy and reduce the extrusion effect; too high an extrusion ratio will make it difficult to extrude, increase the internal stress of the rod, and cause the alloy rod to undergo early aging during the deformation process, which is not conducive to the subsequent processing of the magnesium alloy material. Therefore, the extrusion ratio can be 10, 15, 20, 25, 30, 35, 40, 45, 50, etc., and all ranges and sub-ranges between the above values; it should be understood that in the implementation scheme, any of the above ranges can be combined with any range of other reaction conditions in the present invention.
[0051] In some embodiments of the present application, calculated by mass percentage, in the magnesium alloy material, the Zn content is 0.5% to 1%, the Ce content is 0.1% to 0.3%, the Nd content is 0.3% to 0.6%, and the balance is magnesium and unavoidable impurity elements. Calculated by mass percentage, in the magnesium alloy material, the Zn content can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc., and all ranges and sub-ranges between the above values; the Ce content can be 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, etc., and all ranges and sub-ranges between the above values; the Nd content can be 0.3%, 0.4%, 0.5%, 0.6%, etc., and all ranges and sub-ranges between the above values; it should be understood that in the embodiment, any of the above ranges can be combined with any range of other reaction conditions in the present invention.
[0052] In some embodiments of the present application, the ultimate compression rate of the magnesium alloy material at room temperature is at least 35%.
[0053] 2. Examples and Comparative Examples
[0054] Example 1
[0055] Step 1: Precisely proportion the amount of each component, melt pure Mg at 700℃~720℃, add pure Zn, Mg-Ce master alloy and Mg-Nd master alloy after melting, and introduce inert gas protection into the furnace at the same time, and keep it at 650℃~700℃ for 30min. Among them, calculated by mass percentage, the Zn content is 0.6wt%, the Ce content is 0.2wt%, the Nd content is 0.4wt%, and the balance is Mg and unavoidable impurities. Calculated by volume percentage, the volume ratio of CO2 and SF6 in the inert gas is 300:1.
[0056] Step 2: The furnace continues to heat up to 720°C ~ 750°C, slowly stir, and after the alloy is melted, keep it warm and let it stand for 20 minutes to obtain a magnesium alloy melt.
[0057] Step 3: Pour the magnesium alloy melt obtained in step 2 into a preheated mold at 200° C. to 350° C., and obtain a magnesium alloy ingot after cooling.
[0058] Step 4: The magnesium alloy ingot obtained in step 3 is homogenized at 400°C for 8 hours.
[0059] Step 5: The homogenized magnesium alloy obtained in step 4 is extruded at 450° C. with an extrusion rate of 2 mm / s and an extrusion ratio of 25:1.
[0060] Step 6: The magnesium alloy obtained in step 5 is subjected to heat treatment at 400°C for 1 h and pre-compressed with a pre-compressed deformation amount of 1% and a strain rate of 10 -3 / s.
[0061] Step 7: The magnesium alloy obtained in step 6 is heat treated at 200°C for 8 hours.
[0062] Example 2
[0063] The adjustment was made on the basis of Example 1, except that the pre-compression deformation was 2.5%, and the remaining steps were exactly the same as Example 1. The obtained magnesium alloy material was marked as S#2.5c-8a.
[0064] Example 3
[0065] The method is adjusted based on Example 1, except that the pre-compression deformation is 4%, and the remaining steps are exactly the same as Example 1. The obtained magnesium alloy material is marked as S#4c-8a.
[0066] Example 4
[0067] The adjustment was made on the basis of Example 1, except that the pre-compression deformation was 6%, and the other steps were exactly the same as Example 1. The obtained magnesium alloy material was marked as S#6c-8a.
[0068] Comparative Example 1
[0069] The adjustment is made on the basis of Example 1, except that after step 5 is completed, step 7 is directly performed without step 6; the operating conditions of each step are exactly the same as those of Example 1. The obtained magnesium alloy material is marked as S#8a.
[0070] Comparative Example 2
[0071] The adjustment is made on the basis of Example 4, except that: after step 5 is completed, only step 6 is performed, and step 7 is no longer performed; the operating conditions of each step are exactly the same as those of Example 4. The obtained magnesium alloy material is marked as S#6c.
[0072] 3. Performance Comparison
[0073] This application focuses on the impact of step 6 and step 7 on the structure of magnesium alloy materials. After observing the microscopic morphology of the magnesium alloy materials obtained by the embodiment and the comparative example, it is found that:
[0074] (1) Figure 1 As shown, the magnesium alloy prepared in Comparative Example 1 has a very small amount of precipitated phase, and the precipitated phase is mainly precipitated along the grain boundary, and the size of the precipitated phase is distributed between 200nm and 2μm. Figure 1 The magnesium alloys prepared in Comparative Example 2 and Example 4 have lens structures due to pre-compression strain, which can be considered as twin structures. There are also a large number of network dislocation structures in the matrix, such as Figure 1 (c) However, it is worth noting that in the magnesium alloy prepared in Example 4, high-density nanodots are enriched at twin boundaries and dislocations, as shown by the red and black small arrows, which indicates that the solute atoms are concentrated at the lattice defects, and the average size of the nano-precipitated phase is between 2 and 20 nm, as shown in FIG. Figure 1 As shown in (d), it can be seen that step 7 will induce some alloy elements to form segregation at the surface defects and precipitate in the form of a large number of nanophases.
[0075] (2) In order to further describe the characteristics of the alloy precipitation phase in Example 4, Figure 2 Shows along [11-20] a-MgHAADF-STEM image of the magnesium alloy prepared in Example 4 taken with an axial incident electron beam and its mapping element distribution diagram. It can be seen from the figure that the alloy elements will form two types of precipitates at the dislocation position. One type of precipitate has less element segregation and uniform contrast, such as Figure 2 (a) As shown by the white arrow; the other precipitate phase has more elements segregated and presents a discontinuous distribution, and the size of the precipitate phase is between 5 and 20 nm, as shown in Figure 2 (a) As shown by the yellow arrows. The distribution of these alloying elements at dislocations and twin boundaries, such as Figure 2 (bd) As shown in the figure. It can be seen from the figure that the alloying elements Zn and Nd are segregated together at dislocations and twin boundaries, while the Ce element is almost not segregated and precipitated at the defect position. It can be seen that the strategy of the present application to induce the segregation and precipitation of alloying elements through defects has obvious selectivity for different alloying elements. The precipitated phase in the magnesium alloy prepared in Example 4 is mainly a nanophase enriched with Zn and Nd elements, and the Ce element is not involved.
[0076] (3) Through the above analysis, it can be seen that after the magnesium alloy is treated in step 6, a large number of dislocations, twins and other defects will be generated in the magnesium alloy matrix. The existence of these defects will induce some alloy elements to segregate at these defect positions and form high-density nanophases when they are treated in step 7. On the one hand, due to the segregation of alloy elements at twin boundaries and dislocations, these lattice defects remain stable during the entire deformation process, thereby improving the strength of the alloy; on the other hand, the nanophase in the matrix will induce Zn and Nd elements to precipitate and strengthen; at the same time, due to the presence of high-density pinned dislocations and twins in the matrix, the stress formed by the dislocations will be concentrated during the subsequent deformation process, thereby synergizing the strength and ductility of the alloy. Therefore, the magnesium alloy material treated in this application, since Ce has the effect of promoting non-basal slip to improve the plasticity of the alloy, even if the Ce element does not participate in segregation and precipitation of nanophases, this application can still improve the strength of the magnesium alloy material without a large loss of plasticity, and finally achieve a synergistic effect of strength and toughness.
[0077] (4) However, if only step 6 is performed after step 5, only high-density dislocations and twin structures exist in the magnesium alloy, and there is almost no precipitation of the second phase. This shows that the combination of step 6 and step 7 is a key step in regulating the formation of alloy elements at dislocation and twin boundaries and the precipitation of high-density nanophases.
[0078] (5) Combination Figure 4The changes in mechanical properties shown were experimentally studied on magnesium alloys under different pre-strain degrees and heat treatment conditions. In general, with the increase of pre-strain loading, the compressive yield strength of the specimens increased significantly. The ultimate compressive strain of the magnesium alloy in Example 1 is 36.39%, while the ultimate compressive strains of the specimens in Examples 2 to 4 are increased to 38.9%, 37.35% and 35.63%, respectively. The results show that compared with the sample in Example 1, the pre-strain + 8h intermediate annealing sample achieved a synergistic effect of strength and plasticity; compared with Example 1, the yield strength of Example 4 was increased by 128%, while there was almost no loss of plasticity, such as Figure 4 (b) As shown. It can be seen that the degree of pre-compression deformation in step 6 has a significant effect on the low-temperature heat treatment strengthening in step 7. As the degree of pre-compression in step 6 increases, the alloy toughening effect obtained in step 7 is better. The reason may be that the content of the alloy precipitated phase in comparative example 1 is very small and the size is large, such as Figure 1 The precipitated phases in the magnesium alloys obtained in Examples 2 to 4 are smaller in size and have a higher density, as shown in FIG. Figure 1 (c, d). Therefore, the strengthening effect of the magnesium alloy obtained in Examples 2 to 4 is better than that in Comparative Example 1. The defects introduced in step 6 gradually increase with the increase of the degree of pre-deformation. These defects are conducive to the segregation of alloy elements to form precipitation phases, such as Figure 1 As shown in (c, d), as the degree of compression pre-deformation in step 6 increases, even if the same step 7 (heat treatment at 200℃ for 8h) is performed, the strength of the alloy gradually increases; at the same time, step 6 combines with the nanophase pinned dislocations and twins formed in step 7 to concentrate the internal stress of the dispersed alloy during the subsequent deformation process, thereby synergizing the strength and plasticity of the alloy.
[0079] In summary, in the method described in the present application, further optimization process is performed by performing step 6 and step 7 to achieve higher strength and plasticity. A large amount of dislocations and twins are introduced into the alloy matrix by step 6 pre-compression strain, and these defects provide active sites for segregation of solute atoms (such as Zn and Nd), and low temperature heat treatment further promotes the segregation of solute atoms at these defects, forming a high-density nano-precipitation phase. These nano-precipitation phases effectively hinder the movement of dislocations by pinning dislocations and twin boundaries, and improve the strength of the alloy. Meanwhile, the presence of these precipitation phases also maintains the plasticity of the alloy by dispersing stress concentration. The combination of pre-compression strain and low temperature heat treatment not only improves the strength of the alloy, but also maintains its plasticity to a certain extent. This is because the high-density nano-precipitation phase and pinning dislocation can disperse the stress concentration formed by dislocations in the subsequent deformation process, thereby achieving the coordinated optimization of strength and plasticity.
[0080] In summary, the combination of pre-compression strain (step 6) and low-temperature heat treatment (step 7) can significantly improve the strength of the alloy without sacrificing plasticity. This method not only provides new ideas for the development of high-performance alloy materials, but also provides an important theoretical basis for understanding and regulating the microstructure of the alloy and its influence on mechanical properties.
[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the technical solution. Ordinary technicians in this field should understand that those modifications or equivalent substitutions of the technical solution of the present application that do not depart from the purpose and scope of the technical solution of the present application should be included in the scope of the claims of the present application.
Claims
1. A method for preparing a magnesium alloy material by regulating lattice defects, characterized in that: The specific steps are as follows: Step 1: First, accurately batch the ingredients, heat pure Mg until it is melted, add pure Zn, Mg-Ce master alloy and Mg-Nd master alloy after melting, and introduce inert protective gas at the same time; Step 2: heating the melt obtained in step 1 to completely melt it, and then keeping it at the temperature for 20 to 30 minutes to obtain a magnesium alloy melt; Step 3: pouring the magnesium alloy melt obtained in step 2 into a preheated mold for die casting, and obtaining a magnesium alloy ingot after cooling; Step 4: heating and homogenizing the magnesium alloy ingot obtained in step 3; Step 5: extruding the magnesium alloy treated in step 4 at 350° C. to 450° C., with an extrusion rate of 1 to 10 mm / s and an extrusion ratio of 10 to 50; Step 6: The magnesium alloy treated in step 5 is subjected to a heat treatment at 300°C to 450°C for 1 to 12 hours, and subjected to a pre-compression deformation treatment; wherein, the pre-compression deformation is 1% to 15% calculated according to the percentage of length change, and the strain rate is 10 -2 ~10 -4 / s; Step 7: heat treating the magnesium alloy obtained in step 6 to obtain the magnesium alloy material; Calculated by mass percentage, in the magnesium alloy material, the Zn content is 0.5% to 1%, the Ce content is 0.1% to 0.3%, the Nd content is 0.3% to 0.6%, and the remainder is magnesium and unavoidable impurity elements.
2. The method according to claim 1, characterized in that: In step 7, the heat treatment is: keeping warm at 100° C. to 260° C. for 2 h to 24 h.
3. The method according to claim 1, characterized in that: In step 4, the conditions for the heating homogenization treatment are: homogenization treatment at 400° C. to 480° C. for 8 h to 24 h.
4. The method according to claim 1, characterized in that: In step 1, pure Mg is melted at 700°C to 720°C; the inert gas is a mixture of CO2 and SF6; after the inert protective gas is introduced, the temperature is kept at 650°C to 700°C for 20 to 40 minutes.
5. The method according to claim 4, characterized in that: In the mixed gas, the volume ratio of CO2 and SF6 is (200~400):
1.
6. The method according to claim 1, characterized in that: In step 2, the melt is heated to 720° C. to 750° C. and then kept warm.
7. The method according to claim 1, characterized in that: In step 3, the mold is preheated to 200°C to 350°C.
8. The method according to claim 1, characterized in that: The ultimate compression rate of the magnesium alloy material at room temperature is at least 35%.